Konsep Memorabilia Sebagai Aspek Marketing pada Perancangan Interior Malang Food Center di kota Malang - Retno Ayu Dwipayanti; Andereas Pandu Setiawan (Intra, 2013)
Aspects of the history contained in the objects of memorabilia compiled as the basis for designing the restaurant to establish an atmosphere and a restaurant marketing competitiveness. Memorabilia itself has a meaning as something that is kept because it is associated with a past history. This concept aims to bring back the atmosphere that existed in 1914-1940 to the present day in the city of Malang. So the effect of that has been adapted to colonial Javanese culture and art deco style design reinforces this concept.